Christian congregation in Brazil and its relationship with music - Mariano, André Luiz de Castro (Seven Editora, 2023)
As we know, the Brazilian religious field is remarkably variable, because even the segments that are of the same line or origin present significant distinctions, many of which are visible even to those who are unaware of the subject. It is also multiple, not only of religions (we know that Brazil is a religious country, with numerous religions cohabiting the same space, even if not always, in harmony), but also the nucleus of specific segments (for example, the syncretism present within the Christian religions), as is the case of the evangelical. DOI:https://doi.org/10.56238/sevened2023.006-032